KANDASNYA KRIMINALISASI PERKARA PERDATA MURNI - Sholahuddin Harahap (Jurnal Yudisial, 2011)
ABSTRACTTGHC, ETRL and PTGI (the three legal companies established under the laws of British Virgin Island) have agreed to hold an agreement set forth in notarial deeds. In practice, there were conflicts of management, ownership of shares, and breach of contract. The parties sued each other. The judiciary, in this case the High Court of British Virgin Island, finally dropped its decision. However, after receiving files from the criminal investigators, public prosecutors still filed the case to the Central Jakarta District Court. The author of this article analyzes the decision of the Central Jakarta District Court over the case. He also distinguished the court rulings between the terms of "ontslag van alle rechtsvervolging" (released from all indictments) and "vrijspraak" (freed because of no wrongdoings).Keywords: agreement, ontslag van alle rechtsvervoling, vrijspraak ABSTRAKTGHC, ETRL dan PT GI (tiga perusahaan hukum yang diririkan berdasarkan hukum British Virgin Island) memiliki perjanjian yang tertuang dalam akta notaris. Dalam prakteknya terjadi konflik dalam manajemen, kepemilikan saham, dan pelanggaran kontrak. Dalam bidang hukum, Pengadilan Tinggi British Virgin Island pada akhirnya mengalahkan terdakwa. Terdakwa melakukan upaya hukum dengan melalui pengadilan negeri Jakarta Pusat dimana salah satu putusannya ialah membebaskan terdakwa lepas dari tuntutan hukum, ontslag van alle rechtsvervolging. Dalam kasus ini, penulis menganalisi putusan PN Jakarta Pusat dimana salah satu putusannya terkait "ontslag van alle rechtsvervolging" and "vrijspraak" (freed because of no wrongdoings).Keywords: perjanjian, lepas dari tuntutan hukum, putusan bebas.